Concomitant high expression of BRAFV600E, P‐cadherin and cadherin 6 is associated with High TNM stage and lymph node metastasis in conventional papillary thyroid carcinoma. (23rd September 2015) - Zhao, Le; Jiang, Rong; Xu, Man; Zhu, Ping; Mo, Xiao‐Mei; Wang, Ni; Chen, George G.; Liu, Zhi‐Min
Summary: Context and Objective: BRAFV600E mutation is the most common activating mutation associated with aggressive behaviours in human tumours including conventional papillary thyroid carcinoma (cPTC). P‐cadherin and cadherin 6 have been shown to be mesenchymal‐associated cadherins and promote cancer cell invasion and metastasis. The purpose of this study was to examine BRAFV600E, P‐cadherin and cadherin 6 expressions in cPTC and to assess the association of their expression with clinicopathological indicators. Methods: BRAFV600E, P‐cadherin and cadherin 6 protein expressions in 80 cPTCs, 61 nodular hyperplasia and 76 normal thyroid tissues were examined by immunohistochemistry. The correlation of their protein expression with clinicopathological indicators of cPTC was statistically analysed. Results: Protein expression of BRAFV600E, P‐cadherin and cadherin 6 was upregulated in cPTC. High protein expression of BRAFV600E, P‐cadherin and cadherin 6 was significantly correlated with high TNM stage and lymph node metastasis (LNM) ( P < 0·001). Furthermore, BRAFV600E, P‐cadherin and cadherin 6 protein expressions were correlated with one another. BRAFV600E high expression combined with both P‐cadherin and cadherin‐6 high expressions had stronger correlation with high TNM stage and LNM when compared with BRAFV600E high expression combined with either P‐cadherin or cadherin‐6 high expression ( P = 0·042, 0·017 for TNM stage and P = 0·003, 0·006 for LNM, respectively) and only BRAFV600E high expression ( P < 0·001 for both TNM stage and LNM). Conclusions: Concomitant high expression of BRAFV600E, P‐cadherin and cadherin 6 is strongly associated with high TNM stage and LNM in cPTC.